2016
DOI: 10.1111/jwas.12342
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Factors Influencing Maturation of Atlantic Salmon, Salmo salar, with Focus on Water Recirculation Aquaculture System Environments

Abstract: Sexual maturation of Atlantic salmon, Salmo salar, is a complex process, with many variables having the capacity to influence the timing and prevalence of maturation and acting as promoters and/or inhibitors of sexual development. Precocious maturation has the capacity to seriously impact production in commercial aquaculture settings, and in response there has been a significant amount of research devoted to understanding this issue in order to develop remedial strategies. Very little research has been conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 164 publications
(274 reference statements)
5
74
0
Order By: Relevance
“…Hatcheries are commonly used to supplement wild salmon stocks; however, an unintended outcome of hatchery rearing practices is that hatchery-reared males often exhibit a shift towards earlier maturation. This has been observed in both Pacific and Atlantic salmon (Larsen et al 2004, Good and Davidson 2016). Water temperature and feed rations at hatcheries are often optimized for high growth, which in turn promotes early maturation (Larsen et al 2019); however, hatchery stocks vary in the proportion of males with premature maturation even when raised under identical conditions suggesting genetic differences in susceptibility to early maturation (Spangenberg et al 2015).…”
Section: Introductionmentioning
confidence: 70%
“…Hatcheries are commonly used to supplement wild salmon stocks; however, an unintended outcome of hatchery rearing practices is that hatchery-reared males often exhibit a shift towards earlier maturation. This has been observed in both Pacific and Atlantic salmon (Larsen et al 2004, Good and Davidson 2016). Water temperature and feed rations at hatcheries are often optimized for high growth, which in turn promotes early maturation (Larsen et al 2019); however, hatchery stocks vary in the proportion of males with premature maturation even when raised under identical conditions suggesting genetic differences in susceptibility to early maturation (Spangenberg et al 2015).…”
Section: Introductionmentioning
confidence: 70%
“…Many fish species exhibit marked morphological changes during sexual maturation cycles (Good & Davidson 2016). Considering that the specimens in this study were sampled during the spawning period and that the chosen length range corresponds to the life stage when the majority of individuals start to consume somatic energy for various reproduction purposes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological mechanisms involved in these decisions are not yet clear (Mangel and Satterthwaite ; Taranger et al. ; Good and Davidson ). However, it has been demonstrated that the minijack rate increases with increased feeding and energy reserves in hatchery‐reared Chinook Salmon juveniles (Larsen et al.…”
mentioning
confidence: 99%
“…Previous research has shown that a fish will mature if the rate of acquisition or attainment of a particular energy-related trait (e.g., growth rate, adiposity, or size) during a critical period exceeds a genetically determined threshold. The physiological mechanisms involved in these decisions are not yet clear (Mangel and Satterthwaite 2008;Taranger et al 2010;Good and Davidson 2016). However, it has been demonstrated that the minijack rate increases with increased feeding and energy reserves in hatchery-reared Chinook Salmon juveniles (Larsen et al 2006;Spangenberg et al 2014).…”
mentioning
confidence: 99%